2012
DOI: 10.2355/isijinternational.52.549
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Decarburized Ferrite Depth of Hypoeutectoid Steel with Simultaneous Oxidation

Abstract: The objective of this paper is to describe a method of calculating the decarburized ferrite depth and scale thickness during heating and cooling for hypoeutectoid steel in ambient atmosphere. The decarburization behavior in hypoeutectoid steel is divided into three regions. In temperature region above A3 ferrite is not formed during decarburization from austenite with a carbon concentration C = 0.0 wt%. In temperature region below A3 (C = 0.0 wt.%) and above A3 (C = C0) the decarburized ferrite forms from aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Nomura et al 8) reported a model predicting the ferrite decarburizing depth of spring steel assuming that no oxidation occurred. Choi et al 9) proposed a model to explain the coupled growth of oxide layers and ferrite decarburization in steels based on phase transformation and diffusion calculation during heating and cooling. Badu et al 10) investigated the influence of relative humidity on oxidation and decarburization.…”
Section: Introductionmentioning
confidence: 99%
“…Nomura et al 8) reported a model predicting the ferrite decarburizing depth of spring steel assuming that no oxidation occurred. Choi et al 9) proposed a model to explain the coupled growth of oxide layers and ferrite decarburization in steels based on phase transformation and diffusion calculation during heating and cooling. Badu et al 10) investigated the influence of relative humidity on oxidation and decarburization.…”
Section: Introductionmentioning
confidence: 99%
“…All are based on Fick's 2nd law. The uncorrected and corrected Van-Ostrand-Dewey equation [5,6,8,22,23] is used for annealing temperatures T a > T G , as well as a Fourier analysis [23]. The Van-Ostrand-Dewey equation is also used and corrected for creating a diffusion model of decarburization that is based on microhardness measurements [21].…”
Section: Theoretical Assessment Of the Thickness Of The Decarburized mentioning
confidence: 99%
“…The Van-Ostrand-Dewey equation is also used and corrected for creating a diffusion model of decarburization that is based on microhardness measurements [21]. For annealing temperatures T a < T G the equations for the calculation of the completely decarburized surface ferrite layers are known [5,9,22,24]. Some equations also take into account the oxidation of the surface [6,9,16,22,24,25].…”
Section: Theoretical Assessment Of the Thickness Of The Decarburized mentioning
confidence: 99%
“…The profiles of carbon concentration changes as a function of time and distance (from steel surface to its center direction) during decarburization. 15) In region (c), which is below A 3 (C = C 0 ), austenite in the matrix is transformed into ferrite + austenite or ferrite + cementite, and the decarburized ferrite phase is formed during the decarburization.…”
Section: -Decarburizationmentioning
confidence: 99%
“…(9) and (10) was calculated by stepwise method suggested by Choi and Zwaag. 15) The stepwise method calculates the depths of scale and decarburized ferrite layer during cooling or heating, based on the model of isothermal heat treatment. The cooling history is divided into discrete isothermal steps, and each decarburized depth and scale thickness are computed at the discrete temperature.…”
Section: -Decarburizationmentioning
confidence: 99%